Importance of Beliefs, Attitudes and Values in the Frame of Human Resource Motivation - MOISE, Claudia (Annals of Spiru Haret University. Economic Series, 2014)
The article deals with a complex and original field of analyse – the role that concepts such as beliefs, attitudes and values can entail in the modern human resources management techniques that are dealing with employee’s motivation. Nowadays employees have a complex approach regarding motivation. Especially when we speak about big organisations such as multinational companies, we will find complex jobs having many tasks and a complicated network of inter-relations within the organisation. In such cases, as we speak about middle and top management positions, employee’s motivation is relying on different types of motivation: intrinsic and extrinsic altogether. The substantiation of an efficient motivational strategy can be based on the link between beliefs, attitudes and values of the employees and their motivation development process.